Hypoxia-driven mobilization of altruistic cancer stem cells in platinum-treated head and neck cancer - Lekhika Pathak; Lekhika Pathak; Lekhika Pathak; Bidisha Pal; Bidisha Pal; Joyeeta Talukdar; Partha Jyoti Saikia; Sorra Sandhya; Wale Tasabehji; Wale Tasabehji; Hong Li; Jyotirmoy Phukan; et al. (Frontiers in Immunology)
BackgroundHead and neck cancers harbor dormant cancer stem cells (CSCs). This study explores how platinum therapy impacts these cells in a non-genetic manner and the role of hypoxia in this process. Previously, we identified a novel population of CSCs exhibiting an “altruistic” phenotype, sacrificing self-renewal to promote niche defense (tumor stemness defense, TSD), potentially protecting a dormant subpopulation of CSCs, the reawakening CSC (R-CSC) retaining stress memory. This TSD phenotype involves the activation of the MYC-HIF2α pathway and, importantly, is linked to a hypoxic tumor microenvironment. We termed these TSD+ CSCs “altruistic cancer stem cells” (A-CSCs). Here we investigated the potential role of tumor hypoxia in the mobilization of TSD+ CSCs to the circulation as a part of niche defense against platinum therapy.MethodsWe isolated CTCs and primary tumor cells from head and neck squamous cell carcinoma (HNSCC) patients undergoing platinum therapy (n = 14). We analyzed the TSD phenotype and markers of hypoxia in these cells. Additionally, we further characterized a previously reported pre-clinical model of platinum-induced tumor stemness to study the link between hypoxia, TSD+ CSC emergence, and mobilization to the circulation and bone marrow.ResultsWe isolated TSD+ CTCs with a hypoxic signature from eight out of 14 HNSCC patients. These cells displayed increased proliferation and invasion upon cisplatin treatment, suggesting a role in niche defense. Our pre-clinical model confirmed that hypoxia directly correlates with the expansion of TSD+ CSCs and their mobilization into the circulation and bone marrow following cisplatin treatment. We demonstrated the protection of R-CSCs by TSD+ CSCs. Notably, inhibiting hypoxia alone with tirapazamine did not reduce TSD+ CSCs, CTCs, or R-CSCs. However, combining tirapazamine with FM19G11, a MYC-HIF2α pathway inhibitor, significantly reduced the platinum-induced expansion of both TSD+ CSCs, CTCs, and the presence of R-CSCs in the bone marrow.ConclusionsThis study reveals that HNSCC patients undergoing platinum therapy can harbor TSD+ CTCs exhibiting an altruistic phenotype and a hypoxic signature. Additionally, the pre-clinical study provides a novel non-genetic mechanism of therapy resistance-the altruistic tumor self-defense. The tumor microenvironment, through the emergence of TSD+ CSCs, appears to act collectively to defend the tumor self-identity by hijacking an altruistic stem cell niche defense mechanism.